(untitled) (Acta Scientiarum. Education, 2015)
The Legenda Beati Petri Gundisalvi was written in the thirteenth century and presents episodes of the life and miraculous deeds attributed to the Dominican Peter González (1190 (?) - 1246). Though often mentioned by the biographers of the Saint, this work has not yet been the subject of a critical edition or of a systematic analysis. Thus, there are many questions related to its production. In this article, this Vita is compared to the Legenda vita Sancti Dominici, hagiography dedicated to Dominic de Guzmán, considered the founder of the Dominican Order. It was the first text written after the papal canonization of Dominic, in the second half of the 1230s, and is attributed to Pedro Ferrando. The focus is on the treatment given to the education of Peter González and of Dominic de Guzmán in these texts. The objective is to identify and to debate whether these works share the same perspective on studying, contributing to the discussion about the formation of a Dominican identity during the thirteenth century.